Rancang Bangun Sistem Informasi Evaluasi Belajar Siswa Madrasah (Si-Esam) - - STMIK Nusa Mandiri, Ishak Kholil (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2020)
Abstract - In the current pandemic era, the use of information technology in learning is certainly very reliable. This is motivated by the limited number of face-to-face classes in learning. But the limitations of the meeting did not become an obstacle to the achievement of learning targets. The application of learning based on information systems in the medium is still very minimal, therefore the author tries to encourage the realization of an application that can be implemented on the learning system in the area. Namely Madrasah Student Learning Evaluation Information System (SI-ESAM.) As a way to help the learning evaluation process in a measurable way to achieve the ability, personality and intelligence of students. So that the learning phase of this pandemic situation continues to run according to academic targets. In the previous learning year, the evaluation of learning was still conducted using conventional methods, namely students were directly in the class and the teacher was the supervisor in one classroom. Of course there are many differences between direct class learning evaluations and electronic learning evaluations / elearning. Diera industrial revolution 4.0 the use of applications as a stone tool for an activity has been widely applied which of course must be supported by the implementation of education, namely the madrasa and its infrastructure, to achieve a standard of eligibility. Therefore the authors propose the application of student learning evaluation information systems at Al-ahya Madrasas in Depok City, to provide convenience in the implementation and use of them for students and teachers. This application is created using the PHP programming language and MySQL database software and is connected through the internet. With the learning evaluation information system that is connected through the internet, it is hoped that this solution will be the best choice for academic achievement in a pandemic situation.Keywords: Information Systems, Madrasas, E-learning Abstract – Dalam era pandemi saat ini, pengunaan teknologi informasi dalam pembelajaran tentu sangat diandalkan. Hal tersebut dilatar belakangi oleh keterbatasan jumlah tatap muka dikelas dalam pembelajaran. Tetapi keterbatasan pertemuan tersebut bukan menjadi halangan untuk pencapaian target pembelajaran. Penerapan pembelajaran berbasis sistem informasi dimadrasah saat ini masih sangat minim, oleh karenanya penulis mencoba untuk mendorong terrealisasi sebuah aplikasi yang dapat diimplementasi pada sistem pembelajaran dimadrasah. Yaitu Sistem Informasi Evaluasi Belajar Siswa Madrasah (SI-ESAM.) sebagai salah satu cara untuk membantu proses evaluasi belajar secara terukur untuk pencapaian kemampuan, kepribadian dan intelegensi siswa didik. Sehingga tahapan pembelajan diera pandemi ini tetap berjalan sesuai target akademik. Pada Tahun pembelajaran sebelumnya, evaluasi pembelajaran masih dilakukan dengan metode konvensional yaitu siswa langsung dikelas dan guru sebagai pengawas dalam satu ruang kelas. Tentu banyak perbedaan antara evaluasi pembelajaran dikelas secara langsung dan evaluasi pembelajaran secara elektronik/elearning. Diera revolusi industry 4.0 pengunakan aplikasi sebagai alat batu untuk sebuah kegiatan sudah banyak diterapkan yang tentunya harus didukung oleh penyelenggaraan pendidikan yaitu pihak madrasah dan infrastrukturnya, untuk pencapaian sebuah standar kelayakan. Oleh karenanya penulis mengusulkan aplikasi Sistem Informasi evaluasi belajar siswa pada Madrasah Al-ahya diKota Depok, untuk memberikan kemudahan didalam pelaksanaan dan pengunaannya bagi peserta didik maupun guru. Aplikasi ini dibuat menggunakan bahasa pemrograman PHP dan perangkat lunak database MySQL dan terkoneksi melaui internet. Dengan adanya Sistem informasi evaluasi belajar elyang terhubung melalui jaringan internet, diharapkan solusi ini menjadi pilihan terbaik untuk pencapaikan akademik diera pandemi.Kata Kunci: Sistem Informasi, Madrasah , E-learning